O-GlcNAc transferase inhibits visceral fat lipolysis and promotes diet-induced obesity - Yunfan Yang (Nature Portfolio, 2020)
Post-translational O-linked β-N acetylglucosamine (O-GlcNAc) modification acts as a nutrient-sensing mechanism. Here the authors report that O-GlcNAc transferase inhibits adipose tissue lipolysis via O-GlcNAcylation of the lipid droplet protein perilipin 1 and thus promotes diet-induced obesity.